TINDAK TUTUR ILOKUSI USTAZ YUSUF MANSUR DALAM ACARA WISATA HATI DI STASIUN TELEVISI ANTV - Mefi Ellini; Novia Juita; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purposes of this study are as follows. The first, to describe the types of illocutionary speech acts that used by Ustaz Yusuf Mansur in the show of Wisata Hati on ANTV television station. Second, to describe the strategies of speech acts that used by Ustaz Yusuf Mansur in the show of Wisata Hati on ANTV. Third, to describe the context of the situation of speech that used by Ustaz Yusuf Mansur in the show of Wisata Hati on television. The data of this study is a form of illocutionary speech act, speak strategies, and context used by Ustaz Yusuf Mansur on television. The method used in this study is themethod refer to the advanced techniques involved free free techniques refer to competent. Based on the study results, it was concluded the following. First, the form of illocutionary speech acts of the most widely used by Ustaz Yusuf Mansur in the show of Wisata Hati on ANTV is representative speech acts and speech act directive. It fits with the illocutionary speech act theory as religious speech containing factual matters raised by religious leaders. Second, the strategy of speech the most widely used by Ustaz Yusuf Mansur is a strategy speak frankly without further ado. Third, the context of the situation of speech in the illocutionary speech act Ustaz Yusuf Mansur speech in the situation relaxed atmosphere sensitive topic, tend to use strategies speak frankly with strings attached positive politeness; sensitive topic in the situation speech a formal atmosphere, tend to use strategies speak frankly with strings attached politeness negative; in the situation of speech topic is not sensitive relaxed atmosphere, tend to use strategies speak frankly without further ado; in the situation of speech, topic is not sensitive formal atmosphere, tend to use strategies speak frankly without further ado.